2014
DOI: 10.30843/nzpp.2014.67.5749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new volatile compounds as lures for western flower thrips and onion thrips in New Zealand and Spain

Abstract: Two glasshouse trials in a capsicum crop near Warkworth New Zealand in January 2011 and two field trials in a nectarine orchard near Lleida Spain in July 2013 were undertaken to determine if trap capture of Frankliniella occidentalis (western flower thrips WFT) and Thrips tabaci (onion thrips OT) could be increased by alternative volatile compounds beyond the known thrips attractant methyl isonicotinate (MI) On blue sticky board traps in the crop in New Zealand none of six alternative compounds tested caught m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…Under plant-odour-enriched conditions the attractiveness of pure methyl isonicotinate proved to be consistently significant, attracting about 70% of the F. occidentalis females. The attractiveness of walking thrips to methyl isonicotinate found in olfactometer experiments support results from greenhouse and field trials with flying thripsmethyl isonicotinate has repeatedly been demonstrated to significantly increase trap catches in various crops (Davidson et al, 2007Broughton & Harrison, 2012;Nielsen, 2013;Teulon et al, 2014;de Kogel et al, 2015).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Under plant-odour-enriched conditions the attractiveness of pure methyl isonicotinate proved to be consistently significant, attracting about 70% of the F. occidentalis females. The attractiveness of walking thrips to methyl isonicotinate found in olfactometer experiments support results from greenhouse and field trials with flying thripsmethyl isonicotinate has repeatedly been demonstrated to significantly increase trap catches in various crops (Davidson et al, 2007Broughton & Harrison, 2012;Nielsen, 2013;Teulon et al, 2014;de Kogel et al, 2015).…”
Section: Discussionsupporting
confidence: 55%
“…Another highly efficient attractant for F. occidentalis is methyl isonicotinate (Davidson et al, 2008), a compound that has only been tentatively identified in plant material (Shimoda et al, 1996). p-Anisaldehyde and methyl isonicotinate have also been demonstrated to significantly increase trap catches of several thrips species in various crops in greenhouses and in the field (e.g., Kirk, 1985;Teulon et al, 1993Teulon et al, , 1999Teulon et al, , 2014Davidson et al, 2007Davidson et al, , 2015Broughton & Harrison, 2012). However, the reported increase in thrips captures differ between the studies: possibly due to influencing factors such as compound concentration, release rate, type of trap used, trap spacing, crop, and location (field or greenhouse).…”
Section: Introductionmentioning
confidence: 99%
“…91 Recently, a new potential active ingredient for thrips lures, volatile (S)-verbenone, was described from pine pollen. 92 Volatiles with repellent activities can be utilised for disruption of host finding. Applications of methyl-jasmonate and cis-jasmone deterred WFT larvae from feeding and settling, although repeated exposure resulted in a dose-dependent habituation.…”
Section: Allelochemicalsmentioning
confidence: 99%
“…The Y-tube olfactometer results in this study are also consistent with field studies of increased capture of WFT (glasshouse pest species) populations in traps with MI across a wide range of cropping systems (i.e., feeding histories), such as beans (Muvea, 2011), capsicum (Davidson et al, 2007;de Kogel & Teulon, 2007), fallow field (DAJ Teulon & M-C Nielsen, unpubl. ), fruit trees (Broughton & Harrison, 2012;Teulon et al, 2014) and roses (S Broughton, unpubl. ).…”
Section: Discussionmentioning
confidence: 99%
“…To date this has been the only population tested in laboratory bioassays under controlled conditions. Although increased trapping of WFT has been obtained in New Zealand glasshouses when using MI in conjunction with sticky traps (Davidson et al, 2007), variation in trap catches has been recorded (Nielsen, 2013;Teulon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%